INTERPERSONAL COMMUNICATION OF SINGLE PARENT PARENTS IN EDUCATING THEIR CHILDREN ON RELIGIOUS EDUCATION IN IVORY BLOCK GADING XX LR. PERTANIAN KLAMBIR V - Tambunan, Nurhalima; Hasibuan, Effiati Juliana (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the interpersonal communication of single-parent parents in educating their children on religious education in the Gading block of Dusun XX Lorong Pertanian Klambir Lima Kebun. The method in this study is to use a qualitative approach with a case study approach on parents who have children, especially single parents to examine how they conduct religious education in children. Interviews were addressed to single-parent parents or whose spouses had separated or died in applying religious education to their children, in addition to interviews with village heads and community leaders and supported by other primary data, namely documentation and observations in the field.